Caladium x hortulanum Caladium: FPS83/FP083, 5/2007 - Gilman, Edward (EDIS, 2007)
This document provides an overview of Caladium x hortulanum, commonly known as caladium. It details the plant’s characteristics, including its arrow-shaped foliage, color variations, and growth habits. The document highlights caladium’s uses in landscaping, such as ground cover, edging, and container planting. It also covers planting guidelines, care instructions, and potential pest issues. Additionally, it mentions popular caladium cultivars and their distinctive features. Original publication date October 1999.